The process of co‐designing a model of social prescribing: An Australian case study - Candice Oster; Ashleigh Powell; Claire Hutchinson; Debra Anderson; Bill Gransbury; Martin Walton; Jenny O'Brien; Susan Raven; Svetlana Bogomolova (Health Expectations)
Abstract Introduction Social needs such as housing, employment, food, income and social isolation are having a significant impact on individuals, families and communities. Individuals are increasingly presenting to health settings with social needs, which are ill‐equipped to address nonmedical needs. Social prescribing is a systematic approach connecting the health, social and community sectors to better address social needs and improve health and wellbeing. Social prescribing interventions are being implemented world‐wide. With variability in health and social care systems internationally, it is important that social prescribing interventions are co‐designed with key stakeholders to ensure they can be implemented and sustained within local systems. Methods This Australian case study provides a detailed description of the process undertaken to co‐design a social prescribing service model in a regional area. Four co‐design workshops were undertaken, two with health and social care professionals and two with community members. The project followed an iterative process of resourcing, planning, recruiting, sensitising, facilitation, reflection and building for change across the workshops. Results Through this process, key stakeholders were able to successfully co‐design a social prescribing model of care for the region. Conclusion By demonstrating the process and materials used in our project, we aim to open the ‘black box’ of co‐design for social prescribing and provide ideas and resources for others to adapt and utilise. Patient or Public Contribution The project was designed and undertaken by a steering committee comprising university‐based researchers (authors C. O. and S. B.), local government (author D. A.) and health, social and community services (authors B. G., M. W., J. O. and S. R.). Members of the steering committee participated in project design, participant recruitment, workshop facilitation, data analysis and interpretation.